Hip-hop Islam: commodification, cooptation and confrontation in Southeast Asia - Nasir, Kamaludeen Mohamed (Journal of religious and political practice, 2018)
This article examines the evolution of hip-hop culture in Southeast Asia. Although it has been relatively slow in coming, young Muslims in Indonesia, Malaysia and Singapore have embraced the music genre with much enthusiasm since the 1990s. Generally, Malay youth involvement in hip-hop comes as a challenge to both religious authorities-who do not see the elements present in hip-hop culture as in line with Islamic values-and the state which deems the genre as incompatible with conservative Asian values. This explosion in the popularity of hip-hop has invited high profile statements from political elites from all three countries, professing their concerns about the future of the young. This study demonstrates the embedded socio-cultural complexities of the region, the sophisticated ways in which millennials manoeuvre around these social sanctions and how hip-hop has developed from a stigmatised art form to one that has been coopted at all levels from grassroots Muslim organisations to government ministries.